FLASH Radiotherapy Using Single-Energy Proton PBS Transmission Beams for Hypofractionation Liver Cancer: Dose and Dose Rate Quantification - Wei, Shouyi; Lin, Haibo; Choi, J. Isabelle; Press, Robert H.; Lazarev, Stanislav; Kabarriti, Rafi; Hajj, Carla; Hasan, Shaakir; Chhabra, Arpit M.; Simone, Charles B.; Kang, Minglei (Frontiers in Oncology, 2022)
Purpose This work aims to study the dose and ultra-high-dose rate characteristics of transmission proton pencil beam scanning (PBS) FLASH radiotherapy (RT) for hypofractionation liver cancer based on the parameters of a commercially available proton system operating under FLASH mode. Methods and Materials An in-house treatment planning software (TPS) was developed to perform intensity-modulated proton therapy (IMPT) FLASH-RT planning. Single-energy transmission proton PBS plans of 4.5 Gy × 15 fractions were optimized for seven consecutive hepatocellular carcinoma patients, using 2 and 5 fields combined with 1) the minimum MU/spot chosen between 100 and 400, and minimum spot time (MST) of 2 ms, and 2) the minimum MU/spot of 100, and MST of 0.5 ms, based upon considerations in target uniformities, OAR dose constraints, and OAR FLASH dose rate coverage. Then, the 3D average dose rate distribution was calculated. The dose metrics for the mean dose of Liver-GTV and other major OARs were characterized to evaluate the dose quality for the different combinations of field numbers and minimum spot times compared to that of conventional IMPT plans. Dose rate quality was evaluated using 40 Gy/s volume coverage (V40Gy/s). Results All plans achieved favorable and comparable target uniformities, and target uniformity improved as the number of fields increased. For OARs, no significant dose differences were observed between plans of different field numbers and the same MST. For plans using shorter MST and the same field numbers, better sparing was generally observed in most OARs and was statistically significant for the chest wall. However, the FLASH dose rate coverage V40Gy/s was increased by 20% for 2-field plans compared to 5-field plans in most OARs with 2-ms MST, which was less evident in the 0.5-ms cases. For 2-field plans, dose metrics and V40Gy/s of select OARs have large variations due to the beam angle selection and variable distances to the targets. The transmission plans generally yielded inferior dosimetric quality to the conventional IMPT plans. Conclusion This is the first attempt to assess liver FLASH treatment planning and demonstrates that it is challenging for hypofractionation with smaller fractional doses (4.5 Gy/fraction). Using fewer fields can allow higher minimum MU/spot, resulting in higher OAR FLASH dose rate coverages while achieving similar plan quality compared to plans with more fields. Shorter MST can result in better plan quality and comparable or even better FLASH dose rate coverage.